Comparison of Drug-Free Remission after the End of Phase III Trials of Three Different Anti-IL-23 Inhibitors in Psoriasis - Chang-Yu Hsieh; Francis Li-Tien Hsu; Tsen-Fang Tsai (Adis, Springer Healthcare, 2024)
Abstract Introduction Knowing the remission duration after biologics discontinuation in patients with psoriasis is important, especially when disease relapse is defined as the restart of systemic agents, because it also reflects the real-world clinical practice when topical treatment alone is not adequate for disease control, and a systemic treatment, including biologic, is needed. Biologics are currently indicated for patients with psoriasis who are candidates for systemic treatments. Methods We included 42 patients who were followed up with regularly after the end of risankizumab, guselkumab and mirikizumab trials and investigated the drug-free remission (DFR). A Kaplan-Meier survival analysis and Cox regression model were employed to identify the possible risk factors for relapse. Results Overall, 38/42 (90.5%) patients experienced relapses after discontinuing trial biologics during the follow-up period of at least 96 weeks and up to 227 weeks. In all patients with relapse, the median DFR was 104 days. Kaplan-Meier survival analysis revealed a significant 1-year drug-free survival (DFS) difference between risankizumab (Z) and guselkumab (T) + mirikizumab (M) (p = 0.0462). A difference in DFS curves was noted when patients were categorized by disease duration > or ≤ 2 years (p = 0.1577) and maintenance of a psoriasis area and severity index score (PASI) of 90 at the end of trials (p = 0.1177). Univariate Cox regression model identified that age [hazard ratio (HR) = 1.030 (1.000-1.060), p = 0.0467] and disease duration [HR = 1.046(1.009-1.084), p = 0.0134] were significantly associated with relapse risk. A risk model was established on the basis of multivariable Cox regression results. Risk value = 0.021038 * Age + 0.515628 * Biologic_type (Z = 0,T/M = 1) + 0.025048 * Disease_Duration. The validated patients were divided into two groups by median risk value (1.5). The high-risk group (risk value > 1.5) had a non-significant higher relapse risk than the low-risk group (risk value < 1.5), with a hazard ratio of 1.62 [95% confidence interval (CI) = 0.82-3.23, p = 0.1809]. Conclusion Types of biologics used, disease duration > or ≤ 2 years, and PASI 90 improvement at the end of trial affect the 1-year DFS after biologics discontinuation. Further studies consisting of a larger patient number and longer follow-up period are needed to verify our findings. Trial registration ClinicalTrials.gov identifiers NCT02694523, NCT03047395, NCT02207224, NCT02576431, NCT03482011, and NCT03556202.